Loss of persistence of the North Atlantic Oscillation and its biological implication - Dippner, Joachim W.; Möller, Caroline; Kröncke, Ingrid (Frontiers in Ecology and Evolution, 2014)
Winter sea-level pressure fields in the northern hemisphere were analysed with respect to regimes and regime shifts (RS). Classification of the North Atlantic Oscillation (NAO) patterns resulted in the identification of two longer lasting climate regimes: a persistent NAO− period from 1976 to 1988 followed by a persistent NAO+ period from 1989 to 2000. A further persistent NAO− period from 1956 to 1966 cannot be related to climate regime shifts. After 2000, the NAO lost its persistence and the autocorrelation disappeared, while the variance in the benthic data increased. The consequence was a decrease in potential predictability. The impact of the 1988/89 and 2000/2001 RS on the dominant species and taxonomic groups of benthic macrofauna as well as on benthic community structure was evaluated using an AMOEBA model, a quantitative method used in water management to represent the status of the ecosystem. The model confirmed the effects of the smooth RS in 1988/1989 and the abrupt RS in 2000/2001 on the macrofauna communities provided by earlier data analyses.